1995
DOI: 10.1007/s001250050423
|View full text |Cite
|
Sign up to set email alerts
|

Increased endocytosis in retinal vascular endothelial cells grown in high glucose medium is modulated by inhibitors of nonenzymatic glycosylation

Abstract: SummaryWe sought to determine if hyperglycaemia is responsible for increased retinal vascular endothelial-cell (RVEC) endocytosis in diabetes and to assess the role of nonenzymatic glycosylation in mediation of this novel endothelial-cell pathology. RVECs were propagated in media containing either 5 or 25 mmol/1 glucose for up to 10 days after which they were exposed to the protein tracer horseradish peroxidase for 30 min. The level of RVEC endocytosis was quantified in intact cell monolayers by electron micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 11 publications
(13 reference statements)
0
9
0
Order By: Relevance
“…The in vitro assay used was a novel threedimensional model of angiogenesis that used retinal endothelial cells in an extracellular matrix gel (Matrigel; Becton Dickinson). Bovine retinal microvascular endothelial cells (RMECs) were isolated and cultured between passages 3 and 6 in Dulbecco's modified Eagle's medium (DMEM) (Invitrogen) with 20% porcine serum (Sigma) as previously described (16). RMECs were resuspended in DMEM mixed with an equal volume of Matrigel at 4°C and porcine serum to a final concentration of 20%.…”
Section: Methodsmentioning
confidence: 99%
“…The in vitro assay used was a novel threedimensional model of angiogenesis that used retinal endothelial cells in an extracellular matrix gel (Matrigel; Becton Dickinson). Bovine retinal microvascular endothelial cells (RMECs) were isolated and cultured between passages 3 and 6 in Dulbecco's modified Eagle's medium (DMEM) (Invitrogen) with 20% porcine serum (Sigma) as previously described (16). RMECs were resuspended in DMEM mixed with an equal volume of Matrigel at 4°C and porcine serum to a final concentration of 20%.…”
Section: Methodsmentioning
confidence: 99%
“…An increase in vascular permeability was associated in vitro with endothelial endocytosis. An increase in endocytosis in vascular endothelial cells of the retina has been observed with elevated concentrations of glucose, and this could be reduced by aminoguanidine, suggesting also that this alteration is mediated by the AGEs [125].…”
Section: Ages and Chronic Diabetic Complicationsmentioning
confidence: 97%
“…Short-term diabetic animals also demonstrate a similar increased endocytosis in the retinal vasculature.159 This exaggerated endocytotic effect can be ameliorated by anti-glycation agents such as D-lysine and aminoguanidine, suggesting that the increased endocytosis is an attempt by the cell to replenish its plasma membrane components and receptors which are perceived by the cell as damaged or senescent due to glycation. 160 It is conceivable that in diabetes, glycation of cell membranes interferes with normal plasma membrane recycling and receptor mediated transport of macromolecules.…”
Section: Endocytosismentioning
confidence: 99%
“…Glycational processes culminating in the intra-and extracellular accumulation of reactive end-products and cross-linked proteins can affect the form and function of vascular cells and their extracellular matrices in established diabetes. There is a positive relationship between the incidence and progression of diabetic retinopathy and levels of HbA 1 e and it has been demonstrated that some of the pathological glycational processes can be prevented or minimised by anti glycation drugs in diabetic animal models, 160,173,215,216 suggesting therapeutic applications in the clinical setting. Anti-glycation agents such as aminoguanidine may also inhibit NO synthesis and reduce dysfunction induced by elevated NO levels in diabetes}17 and Stitt et al 178 have used aminoguanidine to reverse vitreous cross-linking mediated by AGEs.…”
Section: Miting Adverse Bioche Mical Processesmentioning
confidence: 99%